MiR‐330‐3p contributes to INS‐1 cell dysfunction by targeting glucokinase in gestational diabetes mellitus. Issue 6 (22nd March 2020) - Xiao, Yuping; Ding, Jingchao; Shi, Yulan; Lin, Long; Huang, Wenyuan; Shen, Dongxia; Wang, Weiqun
Abstract: Aims: High‐expressed miR‐330‐3p in gestational diabetes mellitus (GDM) patients was reported. However, the role and mechanism of miR‐330‐3p in GDM are rarely reported. In this research, we aim to investigate the effects of miR‐330‐3p on GDM. Methods: MiR‐330‐3p expression in the GDM patients' blood was determined by q‐PCR. Blood glucose of blood samples was detected using blood glucose detection kits. Glucokinase (GCK) was confirmed to be a target gene of miR‐330‐3p by bioinformatics and luciferase analysis. Correlations between miR‐330‐3p with GCK and blood glucose were analyzed by Pearson correlation analysis. After INS‐1 cells were treated with glucose and transfected with mimic, inhibitor or siGCK, GCK expression was detected by western blot, and q‐PCR, enzyme‐linked immunosorbent assays, cell counting kit‐8 and Annexin‐V/propidium iodide were conducted to examine the expression of insulin, cell viability and apoptosis. Results: MiR‐330‐3p was high‐expressed in GDM patients' blood, while GCK was low‐expressed. The miR‐330‐3p expression level positively correlated with blood glucoseand and it was highly expressed in glucose‐treated INS‐1 cells (11 and 22 mmol/L), while miR‐330‐3p expression negatively correlated with GCK expression. GCK expression was inhibited by miR‐330‐3p mimic and enhanced by the miR‐330‐3p inhibitor. MiR‐330‐3p mimic inhibited INS‐1 cells' insulin expression, cell viability and induced apoptosis. Yet miR‐330‐3p inhibitor and siGCK exhibited opposite effects which miR‐330‐3p mimic and GCK played on INS‐1 cells. In addition, siGCK reversed the effect of miR‐330‐3p inhibitor on INS‐1 cells. Conclusion: Our findings proved that miR‐330‐3p targeting GCK lead to the dysfunction of INS‐1 cells in GDM, and could become a therapeutic target for GDM treatment.